INDEKS KUALITAS INFRASTRUKTUR JARINGAN IRIGASI DI KABUPATEN SIKKA - Yono Putra; Dedi Imanuel Pau; Maria Kurniaty Lete (Program Studi Teknik Sipil, 2024)
Based on Minister of Public Works Regulation Number 14/PRT/M/2015 dated April 21, 2015, Sikka Regency has 35 irrigation areas under the authority of the Regency where the irrigation network channels water to an area of 3,106 hectares of rice fields; In 2024, the Sikka Regency Government will handle 3 irrigation networks, 2 of which are the Koro irrigation network and the Kojablo Irrigation Network. The quality of the infrastructure facilities handled by the Government needs to be analyzed and maintenance and repairs need to be carried out if they are damaged so that the irrigation network infrastructure facilities can function optimally in channeling flow to the rice fields. This research is urgent to provide information to readers regarding the quality index of irrigation network infrastructure in the 2 longest irrigation networks in Sikka Regency, namely the Koro irrigation network and the Kojablo irrigation network. The research method used is a case study/field study method, then the data is processed and analyzed using Microsoft Office Excel version 19 and conclusions are drawn. The research results show that the infrastructure quality index for the Koro irrigation network is 31%, and the Kojablo irrigation network is 86%. The percentage index for the condition of the irrigation network from both locations is 58,50%, based on Ministerial Regulation Number 12/PRT/M/2015, the percentage value for the condition of the irrigation network is in the moderately damaged category.